Negative Traits of Queen Jadis in C. S. Lewis’ the Chronicles of Narnia: The Magician’s Nephew - Ariyani, Luh Tu; Suwastini, Ni Komang Arie; Artini, Ni Nyoman; Agustini, Dewa Ayu Eka; Rismadewi, Ni Wayan Monik; Pradana, Wayan Radita Yuda; Rewa, Gde Arys Bayu (Universitas Negeri Surabaya, 2025)
As an antagonist in C.S. Lewis’s The Magician’s Nephew, Queen Jadis is narratively required to be depicted as a negative character. This study aimed to analyze Queen Jadis’ negative traits and how they strengthened her role as an antagonist through textual analysis in Miles, Huberman, and Saldana’s interactive qualitative data analysis model. The study showed that Queen Jadis was depicted as ruthless, arrogant, authoritarian, and cowardly, creating conflict and tension in the storyline. Queen Jadis was depicted as ruthless and arrogant to those weaker than her. She destroyed the entire world of Charn by using the Deplorable Word for her desires. When brought to the human world, she showed a dominant trait and used her power to control others. Her cowardice was most strongly shown when she fled at the sign of defeat. While these results show that Queen Jadis’s characterizations made her a proper antagonist for the children-heroes in the novel, her failure in conquering the worlds beyond Charn and loss of magical power function as punishment for these negative traits, sending a moral message to avoid building evil characters for the readers.